On a sum with a three-parameter Mittag-Leffler function. Issue 8 (2nd August 2016) - Oliveira, D.S. de; Capelas de Oliveira, E.; Deif, Sarah
ABSTRACT: The bounding of the two-parameter Mittag-Leffler function is discussed. As a particular consequence, we present two proofs for a sum involving a three-parameter Mittag-Leffler function. This sum can be seen as a generalization of a relation involving a product of two exponential functions. Particular cases are recovered.